Patterns and ecological consequences of water uptake, redistribution, and loss in tallgrass prairie - O'Keefe, Kimberly (Kansas State University, 2016)
Water availability is a key driver of many plant and ecosystem processes in tallgrass prairies, yet we have a limited understanding of how grassland plants utilize water through space and time. Considering that tallgrass prairies experience tremendous heterogeneity in soil resources, identifying spatiotemporal variation in plant ecohydrology is critical for understanding current drivers of plant responses to water and for predicting ecosystem responses to future changes in climate. Here, I investigated the patterns, drivers, and ecological consequences of plant water use (e.g., water uptake, water redistribution, and water loss) in a native tallgrass prairie located in northeastern Kansas, USA. Using a combination of leaf gas exchange, sap flow, and isotopic techniques, I addressed four main questions: 1) How does fire and grazing by bison impact use of water from different sources and niche overlap for common grasses, forbs, and shrubs? 2) Does hydraulic lift occur in grazed and ungrazed tallgrass prairie, and does this impact facilitation for water within grassland communities? 3) What are the patterns and drivers of nocturnal transpiration in common grassland species? 4) How does diel stem sap flow and canopy transpiration vary among common grassland species? I found that bison grazing increased the depth of water uptake by Andropogon gerardii and Rhus glabra, reducing niche overlap with co-occurring species. Conversely, grazing did not affect hydraulic lift, which was generally uncommon and likely limited by nocturnal transpiration. Further, leaf gas exchange measurements indicated that nocturnal transpiration occurred commonly in tallgrass prairie plants and was greatest among grasses and early in the growing season. Nocturnal transpiration was not driven by vapor pressure deficit or soil moisture, as commonly observed in other systems, but was regulated by nocturnal stomatal conductance in most species. Finally, I found that daytime sap flow rates were variable among species and functional types, with larger flux rates among woody species. Nocturnal sap flow rates were more consistent across species, which caused nighttime sap flow and transpiration to account for a larger proportion of daily flux rates in grasses than in forbs or shrubs. These results show that water uptake, water redistribution, and water loss are all influenced by different biotic and abiotic drivers and have varying ecological impacts across a heterogeneous landscape. Additionally, extensive differences in water flux exist among co-occurring species and plant functional groups, which likely reflect varying strategies to tolerate water limitation. These results suggest that shifts in the abundance of these species with future climate changes, or with ecosystem state changes, will likely impact ecosystem-level water balance.
Keywords: Grasslands; Transpiration; Isotopes; Sap flowPlant physiology